An efficient reverse genetics platform in the model legume Medicago truncatula. Issue 3 (11th November 2013) - Cheng, Xiaofei; Wang, Mingyi; Lee, Hee‐Kyung; Tadege, Million; Ratet, Pascal; Udvardi, Michael; Mysore, Kirankumar S.; Wen, Jiangqi
Summary Medicago truncatula is one of the model species for legume studies. In an effort to develop legume genetics resources, > 21 700 Tnt1 retrotransposon insertion lines have been generated. To facilitate fast‐growing needs in functional genomics, two reverse genetics approaches have been established: web‐based database searching and PCR‐based reverse screening. More than 840 genes have been reverse screened using the PCR‐based approach over the past 6 yr to identify mutants in these genes. Overall, c. 84% (705 genes) success rate was achieved in identifying mutants with at least one Tnt1 insertion, of which c. 50% (358 genes) had three or more alleles. To demonstrate the utility of the two reverse genetics platforms, two mutant alleles were isolated for each of the two floral homeotic MADS‐box genes, MtPISTILATA and MtAGAMOUS. Molecular and genetic analyses indicate that Tnt1 insertions in exons of both genes are responsible for the defects in floral organ development. In summary, we have developed two efficient reverse genetics platforms to facilitate functional characterization of M. truncatula genes.